Anticipation of vertebral pedicle breach through dynamic surgical guidance - Williams,John (2014)
OBJECTIVE: To determine the effectiveness of a pedicle probe to anticipate an impending breach and allow redirection during placement of a pilot pedicle hole. METHODS: Purposely four cortical wall sites were drilled: medial and lateral pedicle wall, and lateral and anterior wall of the vertebral body. The surgeon stopped probing when the sound changed, suggesting abutment against the cortical wall ("anticipation" of impending breach). A fluoroscopy image was then obtained. The surgeon then advanced the PediGuard through the cortex until the sound changed, indicating a breach. In the second part of the study three probes were used: 1) DSG (PediGuard) with curved tip with electronics ON; 2) DSG with electronics OFF; 3) standard Lenke probe. After the images were taken, the operating surgeon (blinded to x-rays) was instructed to redirect and continue drilling into the vertebral body. RESULTS: The surgeon accurately anticipated 60 of 75 (80%) of the breaches, 17 of 19 (89%) in the medial pedicle wall. In the second part of the study the DSG with electronics ON was superior to the DSG with electronics OFF as well as the standard Lenke probe (100% vs. 90% vs. 79%, p = 0.0191). CONCLUSION: Successful redirection by passing the pedicle probes into the vertebral body without a breach after anticipation of an impending pedicle wall breach occurred in 100% of the drillings when done with the DSG with the electronics ON vs only 84% when there was no electronic feedback.